Combined Sialendoscopic and Transoral Approach for Large Submandibular Intraparenchimal Stones. (2nd September 2014) - Gallipoli, Camilla; Pagliuca, Giulio; Martellucci, Salvatore; De Vincentiis, Marco; Fusconi, Massimo; Greco, Antonio; Gallo, Andrea
Abstract : Objectives: (1) Describe a combined sialendoscopic and transoral approach to remove large intraparenchymal submandibular sialoliths. (2) Assess functional results after stone removal. Methods: Eighteen consecutive patients with large submandibular hilar stones with intraparenchymal extension were enrolled in this prospective study at the ENT University Unit of the "A. Fiorini" Hospital, "Sapienza" University of Rome, from April 2011 to June 2013. In all cases the size of sialoliths (median diameter 1.8 cm, range 0.9‐2.2 cm) prevented sialendoscopic intraductal removal even after lithotripsy. The diagnosis was confirmed by ultrasound examination and, in selected cases, by computed tomography imaging. In all cases a combined sialendoscopic and transoral approach was accomplished by performing a deep incision of the mouth floor at the submandibular hilus level after endoscopic visualization of the stone. Three months after surgery an ultrasound examination was re‐run to detect the presence of residual sialoliths. Pre‐ and intraoperative findings, surgical times, follow‐up data, and functional results were analyzed. Results: Intraparenchymal stones were successfully removed using the combined technique in all cases. Fifteen patients (83.5%) were symptom‐free after 6 months of follow‐up. Two out of 3 still‐symptomatic patients showed residual sialolithiasis at postoperative ultrasonography. Conclusions: The outcomes of this preliminary study suggest that combined sialoendoscopic and transoral approach is an efficient technique for the removal of large intraparenchymal calculi, which may avoid resorting to sialoadenectomy and thus decrease risk of nerve damage or salivary fistulae.